Real-time nanomechanical and topographical mapping on live bacterial cells-brevibacterium casei under stress due to their exposure to Co2+ Ions during microbial synthesis of Co3O4 nanoparticles - Kumar, Umesh; Vivekanand, K.; Poddar, Pankaj (Journal of Physical Chemistry B, 2009)
The study of elastic properties of microbial and mammalian cells using atomic force microscopy, with force-sensitivity as high as pico-Newtons and spatial resolution of a few nanometers, is proving to be a great tool for the real-time observation of the effects of drugs, biomolecules, metal ions, and nanoparticles on cell physiology in their natural environment. It has been shown that the Young's modulus of the cell surfaces is extremely sensitive to the surrounding environment. Recently, a broad array of microbes have been used successfully to synthesize nanocrystals of several metal and metal oxides in a controlled manner at room temperature after exposing them to various metal ion precursors. However, so far there is no report on the fate of their elastic properties and cell topography etc. during and after their exposure to the metal ions during the microbial synthesis of nanomaterials. Additionally, this information is also found to be extremely relevant to areas such as bioremediation, bioleaching, and biomineralization, where it is important to study the direct influence on the cell physiology in the presence of metal ions. Here, we report, for the first time, the use of AFM force-distance curves on live cells, to directly monitor (in real time) the changes in the surface-topography, surface-adhesion, indentation-depth, and Young's modulus of a metal-tolerant marine bacterium, Brevibacterium casei, isolated from the coast of the Arabian Sea, after its exposure to the Co2+ ions during the process of biosynthesis of nanoparticles. We earlier reported that this bacterium is capable of using the cobalt acetate as a precursor to synthesize protein-functionalized Co3O4 nanoparticles with very high crystallinity. Our study indicates a significant change in the morphology as well as elastic and adhesive properties of the Brevibacterium casei, where we found an increase in the adhesive properties and the indentation depth of the bacterial surfaces and a decrease in the cell stiffness after several hours of exposure to the cobalt acetate. We have discussed both qualitative and quantitative analysis of the force-spectroscopy data in detail.